Male Sexual Dysfunction and Chronic Kidney Disease - Edey, Matthew M. (Frontiers in Medicine, 2017)
Male sexual dysfunction is common in chronic kidney disease, particularly in end-stage renal disease. Historically this cause of considerable morbidity has been under-reported and under-recognized. The ideal approach to diagnosis and management remains unclear due to a paucity of good quality data, but an understanding of the pathophysiology is necessary in order to address the burden of this important complication of chronic kidney disease. This paper will review the endocrine dysfunction that occurs in renal disease, particularly the hypothalamic-pituitary-gonadal axis, discuss the causes of erectile dysfunction, infertility and altered body image and libido in these patients, and suggest appropriate treatment interventions.